New stability conditions for nonlinear time varying delay systems. Issue 9 (3rd July 2016) - Elmadssia, S.; Saadaoui, K.; Benrejeb, M.
Abstract : In this paper, new practical stability conditions for a class of nonlinear time varying delay systems are proposed. The study is based on the use of a specific state space description, known as the Benrejeb characteristic arrow form matrix, and aggregation techniques to obtain delay-dependent stability conditions. Application of this method to delayed Lurie–Postnikov nonlinear systems is given. Illustrative examples are presented to show the effectiveness of the proposed approach.